Online cognitive-behavioral intervention for stress among English as a second language teachers: implications for school health policy - Eze, Angela; Anyebe, Mary O.; Nnamani, Rebecca G.; Nwaogaidu, John C.; Mmegwa, Patricia U.; Akubo, Esther A.; Bako, Victoria N.; Ishaya, Salome N.; Eze, Matthew I.; Ekwueme, Francis O.; Awokwe, Ngozi N.; Ekwueme, Uchechukwu H.; et al. (Frontiers in Psychiatry, 2023)
Introduction Stress is one of the highest-ranked work-related injuries worldwide and has become almost universal among the Nigerian workforce. English as a Second Language (ESL) teachers face enormous work-related threats that lead to occupational stress. When ESL teachers are stressed, students' language development and entire educational progress are at risk. This is mostly underscored as English, though a second language, serves as the language of instruction in Nigerian schools. As a result, managing occupational stress is particularly important for ESL teachers, as it is among the definitive ways of improving ESL learning and overall educational outcomes. This study examined the effectiveness of online cognitive behavioral intervention (o-CBI) in lowering occupational stress among ESL teachers. Method ESL teachers with at least 1 year of experience were among the participants (N = 89). Participants were divided into two groups: the intervention group (N = 44) and the control group (N = 45). For 9 weeks, the experimental group engaged in nine sessions of 2 h of the o-CBI program. The Single Item Stress Questionnaire (SISQ), the Satisfaction with Therapy and Therapist Scale-Revised (STTS–R), and the Teachers' Stress Inventory (TSI) were the measures used to collect primary and secondary data. Four sets of data were collected at baseline, post-test, and follow-up 1 and 2 evaluations. The data were analyzed using mean, standard deviation, t-test statistics, repeated measures ANOVA, and bar charts. Results and discussion Compared to the control group, the o-CBT group had significantly lower TSI scores at the post-test (Time 2) and follow-up evaluations (Times 3 and 4). Between pre-, post-, and follow-up 1 and 2 measurements, there were no significant differences in occupational stress index scores in the control group. It was concluded that o-CBI is effective in job-stress treatment among ESL teachers. In addition, implications for school health policy are discussed. The o-CBI for occupational stress was well received by the participants, showing high acceptability among ESL teachers.